'Reflecting or frozen?' The impact of Covid-19 on art therapists working with people with a learning disability. Issue 3 (3rd July 2021) - Power, N.; Dolby, R.; Thorne, D.
ABSTRACT: Background: A series of online practice development discussions were held during the Covid-19 pandemic by the Art Therapy and Learning Disability Professional Support Group of the British Association of Art Therapists (formerly known as the Special Interest Group). Aims: (1) To capture the experiences of art therapists living through and working with this population during the global pandemic; (2) To describe the barriers and facilitators for online art therapy with people with a learning disability. Methods: An anonymised, hand-written record was made during six 60-minute Zoom sessions. The data was transferred to an Excel database. Reflexive thematic analysis was conducted. Results: The resultant themes and thematic map are shared in this paper. The themes are: (A) The pandemic as leveller. (B) The joy and jeopardy of working online. (C) Art after the eclipse. (D) The function of the professional support group. (E) Insight and understanding to meet client diversity. Conclusions: Stimulated by the national restrictions imposed due to the pandemic, art therapy practice changed at an unprecedented pace. Online art therapy for people with a learning disability may provide a viable alternative to face-to-face art therapy. The BAAT Professional Support Group provides an important peer-network for art therapists and could become a practice-based research hub. Implications: Further research is needed to develop best-practice online art therapy; this must include experts by experience as co-researchers. Additional training will be needed for art therapists to practice safely and confidently online. Plain-language summary: In 2020, the coronavirus made many people across the world sick, some people died. In the UK, our government asked us to stay at home to help to stop the virus spreading. Lots of things changed very suddenly – activities, hobbies and therapy were stopped. This meant that people with a learning disability were not able to keep coming to their art therapy sessions. Art therapists across the UK met on the internet, using a video-chat, to talk about what changes they had made in their clinical practice, whether they were able to keep therapy going during the pandemic and how they felt about the changes. We wanted to understand: (1) Art therapists' experiences during the pandemic. (2) What's helped and what's gotten in the way when art therapists have worked online with people with a learning disability. This piece of research uses a qualitative research procedure called 'thematic analysis' to make sense of different people's views. Thematic analysis is a systematic way of organising and interpreting large volumes of information, called 'data'. In this research, the data is people's words, which were written down live during the six video-chat meetings. Using thematic analysis helps us to find patterns in the data where people have a similar or different view. These patterns are called: 'themes'. The themes gave us a concise record of a broad range of people's views. We found five key themes: (A) The pandemic as leveller. (B) The joy and jeopardy of working online. (C) Art after the eclipse. (D) The function of the professional support group. (E) Insight and understanding to meet client diversity. Online art therapy might help some people with a learning disability, but we need more research and training. Art therapists value peer-support. Our peer-support group could help to develop more robust research projects.